INTERNATIONAL LAW OF THE SEA ENFORCEMENT ON ILLEGAL SEA DEFENCES: A CASE STUDY OF TANGERANG AND BEKASI WATERS - Rizqi Bekti Pratama (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to address the growing problem of illegal sea fencing in Tangerang and Bekasi waters, which has significant negative impacts on marine ecosystems, biodiversity and the livelihoods of local fishing communities. This research explores the effectiveness of international legal frameworks, specifically the United Nations Convention on the Law of the Sea (UNCLOS), in regulating and enforcing maritime activities related to illegal sea fencing in Indonesia. The study will evaluate the role of national law enforcement agencies in addressing illegal practices such as unauthorised fishing, sand mining and smuggling, focusing on jurisdictional challenges and enforcement mechanisms. The benefits of this research are enhancing marine conservation efforts, improving law enforcement practices, supporting coastal communities by protecting their livelihoods, promoting international cooperation in maritime law enforcement, and increasing public awareness of legal compliance to ensure more sustainable use of marine resources. This article emphasises the need for stronger enforcement mechanisms, clearer regulations and better coordination among stakeholders. A more integrated approach, involving local communities alongside the government, is essential to effectively tackle illegal marine fencing and protect the environment and livelihoods of local people. The study also revealed that current legislation does not fully address the complexity of the issue, such as the wider environmental impacts of sea fences and the economic impact on the region.